2004
DOI: 10.1117/12.546789
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of packaged piezoactuators for industrial applications

Abstract: A comparison of different commercially available packaged piezoelectric actuators is presented. The comparisons are based on force, stress and strain performance at similar field densities. A new metric of comparison, based on energy efficiency, is introduced. This paper provides designers with useful information on actuators and actuator performance for industrial applications. The QuickPack® and PowerAct™ actuators remain the only packaged piezoelectric actuators to be produced in high volume and to feature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The signal generator produces voltage waveforms with up to 20 V peak-to-peak amplitude. Since the maximum drive voltage of the patch transducers is approximately 1000 V [14], an increase of the drive voltage amplitude is a simple way to increase the system power throughput beyond values reported in this article.…”
Section: Figure 3 Photograph Of the Three Types Of Piezoelectric Tramentioning
confidence: 82%
“…The signal generator produces voltage waveforms with up to 20 V peak-to-peak amplitude. Since the maximum drive voltage of the patch transducers is approximately 1000 V [14], an increase of the drive voltage amplitude is a simple way to increase the system power throughput beyond values reported in this article.…”
Section: Figure 3 Photograph Of the Three Types Of Piezoelectric Tramentioning
confidence: 82%
“…Recent work carried out at Cardiff University showed that they perform well up to several hundreds of kilohertz, both in the damage detection and the power transmission applications. Due to the low thickness (~0.25 mm) of the piezoelectric material [4] and the dense distribution of electrodes on its surface, the electric field magnitude and consequently the piezoelectric effect in patch transducers is stronger than in crystal transducers. Patch transducers are also fairly flexible and therefore do not have a recognizable resonance frequency (at least in the frequency range investigated in author's work, i.e.…”
Section: Electric Impedance Characterisation Of Piezoelectric Transdu...mentioning
confidence: 99%
“…temperature, humidity, calibration issues) of both the manufacturer and the authors of this work. In fact, contrasting information from the same manufacturer [31,32] indicate that true values might differ from those specified by as much as 37%. • Performing a curve fit for d 31 in figure 14, a polynomial equation can be obtained, thus obtaining a polynomial function for n em using equations ( 26) and (27).…”
Section: Non-linear Voltage-strain Measurementsmentioning
confidence: 99%
“…This variation increases for tensile loads and decreases for compressive loads, until the so-called Buckling load [36][37][38][39] is reached. The Buckling load P b for a cantilever beam is defined in equation (31), where E, I and L are the Young modulus, moment of inertia and beam's length respectively.…”
Section: Mechanical Interactionmentioning
confidence: 99%